2019
DOI: 10.1007/s00415-019-09567-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain is a discriminative biomarker between frontotemporal lobar degeneration and primary psychiatric disorders

Abstract: Due to the significant clinical overlap between frontotemporal lobar degeneration (FTLD) spectrum disorders and lateonset primary psychiatric disorders (PPD), diagnostic biomarkers reflecting the different underlying pathophysiologies are urgently needed. Thus far, elevated cerebrospinal fluid (CSF) levels of neurofilament light chain (NfL) have been reported in various neurological conditions. Furthermore, recent advancements in ultrasensitive analytical methods (e.g., single molecule array, Simoa) have enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 23 publications
8
77
0
Order By: Relevance
“…A further novel contribution of this study is we demonstrate the normal plasma NfL concentrations of individuals with moderate and severe depression, and that high AUC (85%) existed when comparing depressed patients with those with an FTD diagnosis. Therefore, this study shows promise in plasma NfL discriminating between FTD and psychiatric disorders when the signi cant clinical overlap does exist 26 . Our data is also consistent with previous studies on plasma NfL in DS [53][54][55] where an increase of plasma NfL levels were substantially higher in the DSAD group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A further novel contribution of this study is we demonstrate the normal plasma NfL concentrations of individuals with moderate and severe depression, and that high AUC (85%) existed when comparing depressed patients with those with an FTD diagnosis. Therefore, this study shows promise in plasma NfL discriminating between FTD and psychiatric disorders when the signi cant clinical overlap does exist 26 . Our data is also consistent with previous studies on plasma NfL in DS [53][54][55] where an increase of plasma NfL levels were substantially higher in the DSAD group.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, NfL is seemingly not elevated in Parkinson's disease (PD) in comparison to other neurodegenerative disorders and therefore a discrimination can be made from atypical parkinsonian disorders 24,25 . Furthermore, developing evidence demonstrates the potential use of using plasma NfL in discriminating FTD and primary psychiatric disorders 26,27 suggesting a potential differential diagnostic value of blood NfL in certain clinically relevant situations.…”
Section: Introductionmentioning
confidence: 99%
“…NfL is the most promising fluid biomarker for diagnostics and monitoring degeneration in FTD both in the context of clinical practice as well as in clinical trials [ 33 ] In the diagnostic process, NfL is the only fluid biomarker with potential to separate bvFTD from psychiatric disorders [ 34 , 35 ], which constitute the main differential diagnosis for bvFTD [ 36 ]. Plasma is arguably preferable to CSF for NfL measurements due to the minimally invasive procedure required to sample it.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that concentrations of neurofilament light chain (NfL), a marker of axonal damage which is measurable in CSF, plasma or serum, are increased in FTLD and may be related to parameters of disease severity and prognosis (Pijnenburg et al, 2015;Meeter et al, 2016;Rohrer et al, 2016;Wilke et al, 2016;Foiani et al, 2018;Steinacker et al, 2018;Heller et al, 2020;Katisko et al, 2020). Furthermore, a Meso-Scale Discovery (MSD) assay for plasma phospho-Tau181 developed by Lilly Research Laboratories was found to differentiate AD from healthy controls, suggesting its ability to identify mixed 3R/4R tau pathology (Mielke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%